The “creative milieu” — No more than a theoretical concept, or an instrument of regional development? - Fromhold-Eisebith M.A., Martina (Raumforschung und Raumordnung | Spatial Research and Planning, 1999)
Theories of successful regional development which, like the “creative milieu” concept, stress the importance of networks of personal contacts quite rightly attract the interest of those involved in the practice of regional development planning. This article presents some of the key ideas behind this concept and evaluates them with regard to the possibility of translating them into planning instruments. A selection of examples of “creative milieus” both in Germany and abroad serve to highlight the wealth of variety which exists, but also underline the unfeasibility of trying to plan for the regional development processes associated with this concept. The article concludes by advancing a number of ideas which demonstrate how — notwithstanding certain reservations — the milieu approach might still be applied to good effect in regional development.
Keywords: Article